Administrative Land Conflicts and Reforming State-Owned Enterprises in Indonesia - Anshori Ilyas; Hamzah Hamzah (Hasanuddin Law Review, 2022)
Land control and ownership contain the emergence of legal norms including authority, rights, and obligations, as well as power. In juridical, it is a system aiming to protect and encourage values that are strongly embraced by the community. This study presents an up-to-date survey on the conflict between state-owned enterprises (SOEs) and the community in Indonesia. Normative and empirical approach were used in this study. The results showed that state-owned enterprises are more subject to institutional pressures that arise from a weak authority of “state ownership”. This weak authority is developed through the combination of ideological conflicts, perceived threats to national security, and claimed unfair competitive advantage. The results not only extend the institutional theory to explain differential effects on entrants but also demonstrate how foreign investors of idiosyncratic origins proactively build authority in host countries.